Biomethanation of Sugarcane Wastewater by Ultrasonic Membrane Anaerobic System (UMAS) to Produce Methane Gas - Nour, A. H.; Mohd Amirul, Anuar (IJESRT, 2015)
The five largest countries that produce sugar from sugarcane in 2011 were Brazil, Thailand, India, European Union,and China. The demand for sugars nowadays is high, thus, the production of sugar is increasing nowadays, and the sugarcane wastewater increased and caused more pollutions. Therefore, wastewater sugarcane was treated to produce methane by using anaerobic digestion method. But, most of the problem occurs during the treatment process is membrane fouling. Membrane fouling can cause severe flux decline that can affect the quality of the water produced, and the cost to fixed membrane fouling is expensive. Thus, Ultrasonic Membrane Anaerobic System (UMAS) is used as alternative overcome this problem. The sugarcane wastewater had to acclimatize for 5 days before running the reactor. The raw value of COD recorded was 9870 mg/L; BOD was 2480.35 mg/L, TSS 1.976 mg/L, and VSS 1.331mg/L. The pH, pressure, and temperature were kept constant during this experiment with the value 6.5-7.5, 1.5-2.0 bar, and 32OC respectively. After 28 days of experiment, the COD removal efficiency obtained was 95%, BOD removal efficiency was 97% and the methane gas composition obtained was about 75%.The TSS and VSS removal efficiency also reached 99% of removal. Based on the results obtained after 28 days of experiment, UMAS not only can treat high strength wastewater, but also can treat low strength wastewater, avoid membrane fouling and produce methane gas from sugarcane wastewater. Nevertheless, further works are required to provide deeper understanding of the mechanisms involved to facilitate the development of an optimum system applicable to the industry.